Representasi perempuan berkebaya dalam komunitas seni grafis taring padi : kajian semiotika roland barthes terhadap ambiguitas ideologi gender - Viola Dinda Dwi Hapsari; Novita Wahyuningsih (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
This study aims to analyze the representation of kebaya-wearing female figures in Taring Padi's graphic art using Roland Barthes' semiotic framework. The primary focus is the ideological gender ambiguity arising from the utilization of traditional kebaya symbols within progressive post-Reformasi 1998 resistance narratives. The methodological approach employs qualitative descriptive analysis with two-stage semiotics (denotation and connotation) and myth formation mechanisms. Primary data is sourced from the publication Taring Padi: Seni Membongkar Tirani (2011), with the main sample being the poster titled "Berikan Hak Suara Kami Sebagai Perempuan" ("Give Us Our Voting Rights as Women"). Research findings identify three central myths in the construction of the kebaya female figure: "People's Honesty," "Stomach Politics," and "Militant Mother." The study reveals ideological duality; kebaya is operationalized as a symbol of political agency and popular sovereignty, yet simultaneously perpetuates the historical legacy of "State Maternalism" that sustains women's domestication. The analysis affirms that Taring Padi's graphic art serves as a disruptive medium against ruling narratives while functioning as an arena for contesting gender identity meanings in Indonesia.